2019
DOI: 10.4236/ojce.2019.94023
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Method for Cost Assessment of Seismic Mitigation Designs for Reinforced Concrete Buildings According to ECP Code

Abstract: The Earthquake can be considered as a natural phenomenon or a disaster based on the seismic response of structures during a severe earthquake that plays a vital role in the extent of structural damage and resulting injuries and losses. It is necessary to predict the performance of the existing structures and structures at the design stage when it subjected to an earthquake load. Also, it is needed to predict the repair cost required for the rehabilitation of the existing buildings that is insufficient in seism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 2 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…The concept behind the response factor is to integrate nonlinearity with the overstrength, redundancy, and ductility of a structure to accurately assess the seismic force. Figure 1 illustrates the relationship between a structure's base shear (total horizontal load) and its roof displacement, as described by [1][2][3] for nonlinear static analysis. The reduction factor is typically expressed as a function of various structural system factors, including strength, ductility, damping, and redundancy.…”
Section: Response Modification Factormentioning
confidence: 99%
See 4 more Smart Citations
“…The concept behind the response factor is to integrate nonlinearity with the overstrength, redundancy, and ductility of a structure to accurately assess the seismic force. Figure 1 illustrates the relationship between a structure's base shear (total horizontal load) and its roof displacement, as described by [1][2][3] for nonlinear static analysis. The reduction factor is typically expressed as a function of various structural system factors, including strength, ductility, damping, and redundancy.…”
Section: Response Modification Factormentioning
confidence: 99%
“…A structure must be able to withstand intense seismic events without collapsing suddenly, even though it may suffer some structural and nonstructural damage. This is the core principle of earthquake -resistant design, which involves constructing a structure to withstand seismic forces by dissipating energy a nd exhibiting inelastic behavior [1][2][3]. Recent earthquakes have shown that elastic analysis is inadequate for assessing the true seismic performance of reinforced concrete buildings.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations